Learning transfer at skill institutions' and workplace environment: A conceptual framework - Ruhizan, M. Yasin; Y. Faizal, Amin Nur; C. R., Ridzwan; R., Mohd Bekri; Azwin Arif, Abdul Rahim; I. Irwan, Mahazir; Ashikin, H. Tajul (Canadian Centerof Science and Education, 2013)
Efficient human resource management and skills development are central to any organization. However, identified less than 15 to 20 percent of the knowledge and skills acquired in trainings were actually applied in workplaces. Lack of awareness and limited skills learned have caused loss of funds invested in training programs and continued to contribute to mismatches in labour issues. Thus, this conceptual paper proposes key aspects of learning transfer required in training institution based on National Occupational Skill Standards (NOSS) system and in workplace environment. A conceptual framework which is based on critical reviews of current approaches in studies of learning transfer has been devised to highlight the relationship between learning transfer and skills training for today’s workplaces. The framework is a scientifically robust framework for transfer of learning at skill institutions. This study is significant in emphasizing the need for appropriate evaluation methods that can assist practitioners at skill institutions to develop learning transfer in a more credible manner.